2019
DOI: 10.1016/j.jadohealth.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Transition Readiness for Talking With Providers in Urban Youth With Asthma: Associations With Medication Management*

Abstract: All coauthors confirm that there are no known conflicts of interest associated with this publication and there has been no significant financial support for this work that could have influenced its outcome. We confirm that the manuscript has been read and approved by all named authors and that there are no other persons who satisfied the criteria for authorship but are not listed. We further confirm that the order of authors listed in the manuscript has been approved by all of us. We confirm that we have given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Caregivers seemed to be unaware of gaps in their adolescents’ food allergy management and expressed difficulties with their child's transition to independence and their subsequent loss of control . Readiness for transition was associated with greater perceived medication independence, but this was not associated with improved responsibility or medication adherence in the young person . Successful transition required systematic support, developmentally appropriate and adaptive health care from healthcare professionals …”
Section: Resultsmentioning
confidence: 98%
“…Caregivers seemed to be unaware of gaps in their adolescents’ food allergy management and expressed difficulties with their child's transition to independence and their subsequent loss of control . Readiness for transition was associated with greater perceived medication independence, but this was not associated with improved responsibility or medication adherence in the young person . Successful transition required systematic support, developmentally appropriate and adaptive health care from healthcare professionals …”
Section: Resultsmentioning
confidence: 98%
“…As we predicted, both adolescents with ADHD and their caregivers reported that caregivers carry more responsibility for asthma management, compared with caregivers of teens with asthma only. Asthma self-management may be a particular challenge for low-income youth because they are likely to be given responsibility for asthma management at an early age [5]. Caregivers may need to provide additional support to adolescents with ADHD, who have impaired concentration and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the outcome variable of this study was self-reported medication nonadherence, which may have been susceptible to misreporting. Interestingly, teenagers who were "ready" were more likely to be white and have a caregiver who was educated past high school, highlighting the potential role of socioeconomic status [19]. Verma and Rohan [20], who studied resilience and transition readiness among pediatric patients with various chronic illnesses, presented similar findings, reporting that neither transition readiness nor resilience was associated with self-reported or actual adherence, as measured by prescription refill data [20].…”
Section: Transition Readinessmentioning
confidence: 93%
“…Research in populations with pediatric liver transplants, asthma, and IBD have reported conflicting results [17,19,20]. One study looked at the role of transition readiness, specifically readiness to talk with providers and manage daily activities, amongst youth with asthma [19]. These behaviors, as well as perceptions of independence in taking medication, were not related to actual medication adherence.…”
Section: Transition Readinessmentioning
confidence: 99%
See 1 more Smart Citation